2006
DOI: 10.1073/pnas.0604237103
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative deformation of mineral and collagen in bone at the nanoscale

Abstract: In biomineralized tissues such as bone, the recurring structural motif at the supramolecular level is an anisotropic stiff inorganic component reinforcing the soft organic matrix. The high toughness and defect tolerance of natural biomineralized composites is believed to arise from these nanometer scale structural motifs. Specifically, load transfer in bone has been proposed to occur by a transfer of tensile strains between the stiff inorganic (mineral apatite) particles via shearing in the intervening soft or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

35
493
3
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 589 publications
(533 citation statements)
references
References 30 publications
35
493
3
2
Order By: Relevance
“…The composite combines the optimal properties of both constituents to form a remarkably stiff and tough low‐density material 2. Although the larger‐scale bone structure varies depending on bone type and species, the mineralized collagen fibril structure is highly conserved among species and represents the universal building block of bone 12, 13. Collagen–apatite composites are not only the basic building blocks of human bone, but they are also among the most abundant class of biomineralized materials in the animal kingdom 2, 5…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The composite combines the optimal properties of both constituents to form a remarkably stiff and tough low‐density material 2. Although the larger‐scale bone structure varies depending on bone type and species, the mineralized collagen fibril structure is highly conserved among species and represents the universal building block of bone 12, 13. Collagen–apatite composites are not only the basic building blocks of human bone, but they are also among the most abundant class of biomineralized materials in the animal kingdom 2, 5…”
Section: Introductionmentioning
confidence: 99%
“…However, the size and complexity of the structure of mineralized collagen fibrils make it challenging to understand the nanoscale mechanisms governing the fibril mechanics. Other studies based on analytical models have uncovered some key mechanistic features of mineralized tissues where experiments reach their limits, shedding some light on the role of mineral platelets in material strengthening 13, 18, 19, 20, 21, 22. These models help link the nanostructure of the tissue to the organ's mechanical response by integrating some levels of the complex hierarchical structure of bone.…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, this issue is often ignored but has become of importance as in situ testing with high-energy synchrotron x-ray diffraction [25][26][27][28][29][30][31] and tomography imaging [32,33] is now commonly used to identify the micrometer and even sub-micrometer deformation and fracture mechanisms in mineralized tissues.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Nyman et al [36] found that in men's bones the amount of bound water decreased with age, and the toughness decreased concomitantly. Synchrotron radiation can be used in various modes, either as a source of light to examine strains in the different components of bone [22] or for more straightforward tomography, producing images of relatively large specimens [52]. Apart from the capital and running costs of a synchrotron facility, synchrotron radiation is ideal in many ways for doing a whole range of mechanical and characterization studies.…”
Section: New Methods For Characterizing Bonementioning
confidence: 99%
“…There has been progress over the years [17,24,25,43,59]. Recently these efforts have taken on new importance because it is becoming possible to measure the mechanical properties of very small pieces of bone, so the relationship between theory and reality is gradually becoming clearer, though it has not yet arrived [21][22][23].…”
Section: Analysis At the Nano Levelmentioning
confidence: 99%